Risk Factors of Anemia in Preschool Children (3-5 Years Old) in Kedungkandang District, Malang - Rakhmalia Imeldawati; Irwanto Irwanto; Annis Catur Adi (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Anemia is a condition where the mass of red blood cell (RBC) decrease from its normal value. Anemia was caused by some factors such as mother’s education, mother’s age, family income, and cigarette smoke exposure. The purpose of this study is to analyze factors associated with anemia in preschool children. The design of this study was cross-sectional. A cluster sampling was used to select the sample of 281 children. The data obtained from questionnaires and examined hemoglobin levels using hemoglobinometer digital. The data analyze using chi-square test and logistic regression test. The result of the study showed that 32% of preschool children were anemic. The significant factors associated with anemia were mother’s education, mother’s age, family income, and cigarette smoke exposure (p<0.05). We can conclude that need further socialization in the community about food, health and nutrition behaviors, and health and environmental service to prevent anemia in preschool children.